2012
DOI: 10.1111/j.1365-2982.2012.01902.x
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin transporter gene promoter region polymorphisms and serotonin transporter expression in the colonic mucosa of irritable bowel syndrome patients

Abstract: Polymorphism in the promoter region of the SERT gene can influence the expression of SERT mRNA and the levels of the SERT protein in the colonic mucosa, thereby playing a key role in motility-related symptoms of IBS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 39 publications
(89 reference statements)
2
37
0
2
Order By: Relevance
“…A possible relationship exists between SERT-LPR alleles and psychiatric disorders, anxiety-related personality traits, suicide, alcoholism, and responsiveness to antidepressants 65 . Studies of the SERT-LPR in humans with IBS have demonstrated trends in some populations, but a meta-analysis of these findings failed to detect a clear relationship between the SERT-LPR and IBS 66 , although SERT expression level in the gut does appear to be influenced by the SERT-LPR genotype 67 . Furthermore, there appears to be a relationship between the SERT-LPR genotype and depressive symptoms with IBS, with IBS sufferers with the short allele being more likely to have a history of depression 68 .…”
Section: Alterations In Mucosal 5-ht Signaling In Pathophysiological mentioning
confidence: 98%
“…A possible relationship exists between SERT-LPR alleles and psychiatric disorders, anxiety-related personality traits, suicide, alcoholism, and responsiveness to antidepressants 65 . Studies of the SERT-LPR in humans with IBS have demonstrated trends in some populations, but a meta-analysis of these findings failed to detect a clear relationship between the SERT-LPR and IBS 66 , although SERT expression level in the gut does appear to be influenced by the SERT-LPR genotype 67 . Furthermore, there appears to be a relationship between the SERT-LPR genotype and depressive symptoms with IBS, with IBS sufferers with the short allele being more likely to have a history of depression 68 .…”
Section: Alterations In Mucosal 5-ht Signaling In Pathophysiological mentioning
confidence: 98%
“…Once serotonin is secreted from EC cells, SERT will be activated to reuptake serotonin back into EC cells and attenuate the effect of serotonin in GI tracts subsequently [8]. The L variation of 5-HTTLPR is found to increase the expression of SERT gene and enhance SERT activity consequently [9-11,34]. The enhanced SERT activity would take up serotonin and weaken its effects in promoting gut secretion and motility.…”
Section: Discussionmentioning
confidence: 99%
“…However, subsequent studies reported inconsistent results. Kumar et al [102] did show that a SLC6A4 polymorphism was significantly associated with IBS, and Wang et al [103] found that different SERT genotypes could influence SLC6A4 promoter efficiency and SERT mRNA and protein expression in the colonic mucosa.…”
Section: Neurotransmitters and Cytokinesmentioning
confidence: 99%